Monitoring and predicting agricultural drought : a global study - Boken, Vijendra K.; Cracknell, Arthur P.; Heathcote, R. L. (OUP E-Books., 2005)
Accurate monitoring and prediction of agricultural droughts helps manage them, minimize losses attributed to them, and mitigate their extreme forms, which some countries face even today. This book presents the basic concepts of agricultural drought, various remote sensing techniques used to monitor them, and efforts by international organizations to check them.